Puerarin inhibits EMT induced by oxaliplatin via targeting carbonic anhydrase XII - Chen, Xindong; Zhou, Zhiruo; Zhang, Zhi; Zhao, Chenhao; Li, Jiayu; Jiang, Jingwen; Huang, Biao; Qin, Yuan (Frontiers in Pharmacology, 2022)
Puerarin is a flavonoid molecule that widely exists in various plants. Puerarin has been reported to exhibit anticancer effects in various cancers in vitro and in vivo. However, its exact underlying pharmacological mechanism is unclear. This study evaluated the anticancer effect of puerarin combined with oxaliplatin (OXA) in vitro and in vivo. Our results indicated puerarin can reverse platinum-based anti-cancer drug resistance, and enhance the OXA’s anticancer effects on breast cancer. Moreover, puerarin can inhibit migration and reverse the epithelial-mesenchymal transition (EMT) induced by low-dose OXA. Further study showed that the carbonic anhydrase (CA) XII is a potential target of puerarin. In conclusion, puerarin is expected to become an adjuvant chemotherapy drug and can potentially become one of the medicated foods for breast cancer patients.